Platform capitalism's social contract - Niels van Doorn (Internet Policy Review, 2022)
What kind of social contract underwrites platform capitalism? Based on findings from the Platform Labor research project, I discuss a number of ways in which platform companies are expanding their services and influence by identifying particular societal needs and marketing themselves as efficient solutions to workers, citizens and civil society organisations, as well as local governments. I argue that we are seeing the emergence of different gendered "platform fixes", connected to other types of "fixes" that have sought to overcome the limits of capital accumulation and attendant crises of social reproduction. The three platform fixes discussed in this essay each attempt to revise and rearticulate elements of the nation state's social contract, operating at the urban level: 1) Channeling migrant labour into on-demand domestic work; 2) Coordinating civil society's "altruistic surplus" to deliver social care; and 3) Promoting "home-sharing" as a way to finance the rising costs of social reproduction.
Keywords: 300; Capitalism; Digital labour platforms; Digital platforms; Social policy; Inequality